2021
DOI: 10.1093/milmed/usaa266
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Assessment of Tissue Properties During Tourniquet Application

Abstract: Introduction Successful tourniquet application increases survival rate of exsanguinating extremity hemorrhage victims. Tactile feedback during tourniquet application training should reflect human tissue properties in order to increase success in the field. This study aims to understand the mechanical properties of a human limb during tourniquet application. Method Six cadaveric extremities—three uppers and three lowers—were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…During full-text review, study citations were examined, and 20 articles were identified and included. A total of 186 papers 29–31,33–215 were included for data extraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During full-text review, study citations were examined, and 20 articles were identified and included. A total of 186 papers 29–31,33–215 were included for data extraction.…”
Section: Resultsmentioning
confidence: 99%
“…This meant that the biomechanical tissue properties were assumed to be the same, even though multiple tissues comprised the structure. Twenty-one of the included studies assessed tissues as composites 31,37,46,49,51,63,71,72,95,102,103,109,122,136,144,146,155,158,163,170,185 . Of the composites assessed, 6 focused on soft tissue composites (eg, skin and underlying structures), 31,37,102,103,158,185 9 on structures associated with the spine, 46,49,95,109,122,136,146,155,170 5 on joints, 46,63,72,144,163 and 1 on vocal cords 71 …”
Section: Resultsmentioning
confidence: 99%